James McCosh and the Scottish intellectual tradition : from Glasgow to Princeton - Hoeveler, J. David, 1943- (Princeton legacy library, 1981)
James McCosh played a leading role in the effort to reconcile two powerful intellectual and social forces of the nineteenth century: evolution and evangelicalism. In the first modern biography of this philosopher, religious leader, and educator, J. David Hoeveler demonstrates McCosh's significance for Scottish and American philosophy and for American education. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.